Stem cell therapy: A challenge to periodontist - Jayashree A Mudda; Monika Bajaj (Wolters Kluwer Medknow Publications, 2011)
Periodontitis is an inflammatory disease which manifests clinically as loss of supporting periodontal tissues including periodontal ligament, cementum, and alveolar bone, and periodontal therapy is aimed at achieving complete regeneration of these structures. To date, this goal has been tried to accomplish using various bone grafts, growth factors, and barrier membranes. Stem cells are the most fascinating area of biology today and have been used clinically in the field of medicine to treat many incurable diseases. Various human and animal studies have confirmed the presence of stem cells in dental tissues including periodontal ligament. This has opened new avenues aiming toward complete periodontal regeneration using cell-based therapies. This review provides an overview of various types of stem cells in medicine and dentistry and their potential uses especially pertaining to periodontal regeneration.